Ionospheric total electron content of comet 67P/Churyumov-Gerasimenko - Hajra,R; Henri,P; Vallières,X; Galand,M; Rubin,M; Tsurutani,BT; Gilet,N; Bucciantini,L; Nemeth,Z (Astronomy & Astrophysics, 2020)
We study the evolution of a cometary ionosphere, using approximately two years of plasma measurements by the Mutual Impedance Probe on board the Rosetta spacecraft monitoring comet 67P/Churyumov-Gerasimenko (67P) during August 2014–September 2016. The in situ plasma density measurements are utilized to estimate the altitude-integrated electron number density or cometary ionospheric total electron content (TEC) of 67P based on the assumption of radially expanding plasma. The TEC is shown to increase with decreasing heliocentric distance (rh) of the comet, reaching a peak value of ~(133 ± 84) × 109 cm−2 averaged around perihelion (rh < 1.5 au). At large heliocentric distances (rh > 2.5 au), the TEC decreases by ~2 orders of magnitude. For the same heliocentric distance, TEC values are found to be significantly larger during the post-perihelion periods compared to the pre-perihelion TEC values. This “ionospheric hysteresis effect” is more prominent in the southern hemisphere of the comet and at large heliocentric distances. A significant hemispheric asymmetry is observed during perihelion with approximately two times larger TEC values in the northern hemisphere compared to the southern hemisphere. The asymmetry is reversed and stronger during post-perihelion (rh > 1.5 au) periods with approximately three times larger TEC values in the southern hemisphere compared to the northern hemisphere. Hemispheric asymmetry was less prominent during the pre-perihelion intervals. The correlation of the cometary TEC with the incident solar ionizing fluxes is maximum around and slightly after perihelion (1.5 au < rh < 2 au), while it significantly decreases at larger heliocentric distances (rh > 2.5 au) where the photo-ionization contribution to the TEC variability decreases. The results are discussed based on cometary ionospheric production and loss processes.